The Term of Language Variety Spoken by The Employees of Direktorat Deposit dan Pengembangan Koleksi Perpustakaan (Kelompok KCKR) in Perpustakaan Nasional RI - Clara Yustika Azhari; Dewi Nuryanti (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2022)
This research aimed to see the use of language variety in the Kelompok KCKR Perpustakaan Nasional RI. The data was taken by recording some utterances by the employees during their daily interactions. The method used is qualitative with the theory by Wardhaugh (2006). The result showed that speakers used formal and informal words in talking to different addressees, regarding their age, distance among speakers, and position. There are certain words used to show solidarity, to show the ethnics’ belonging, and to be clear in their conversations.